(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2014)
In this work I attempt a reformulation of Lewis’ Best System Account, explicitating the underlying formal conception of scientific theories and trying to define the concepts of simplicity, strength and balance. This essay is divided in three sections. In the first one I introduce the Best System Account of natural laws and formulate the need for its improvement. In the second section I outline a formal framework where the notions of deductive system and scientific theory can be defined precisely. In the last section the notions of simplicity, strength and balance are analyzed. To conclude I argue that the framework proposed does indeed provide the precision required. In addition, it also offers interesting insights on the plurality of concepts of simplicity, strength and balance, and on the general enterprise of formalizing scientific theories.